THU0082 Lung involvement in acpa positive subjects: a pilot study on the role of laboratory, functional and imaging markers. (15th June 2017) - Lucchino, B; Gerardi, MC; Iannuccelli, C; Guzzo, MP; Paolo, M Di; Bonini, M; Vaccaro, F; Palange, P; Vullo, F; Diacinti, D; Valesini, G; Franco, M Di
Abstract : Background: The ACPA-positive Rheumatoid Arthritis (RA) is a complex disease. Signs of immune activity against citrullinated proteins may be present years before the onset of clinical manifestations. Recent findings suggest that the lung may represent an early site of autoimmune-related injury in ACPA-positive patients without signs of arthritis. Objectives: The purpose of the present study was to evaluate the presence of subclinical pulmonary abnormalities in ACPA-positive subjects without arthritis and in RA-patients through laboratory, functional and imaging markers. Methods: Eleven ACPA-positive subjects without arthritis, 10 patients naïve to therapy with early ACPA-positive RA (<6 months duration) and 9 with established ACPA-positive RA (<36 months duration) were consecutively enrolled. Subjects underwent baseline pulmonary function tests (PFTs), DLCO measurement and CPET. The evaluation of Surfactant protein D (SP-D) serum levels was performed in all the patients and in 9 healthy controls matched for age and sex with an ELISA test. Twenty-four subjects underwent chest high-resolution computer tomography (HRCT), in order to evaluate parenchymal or airways abnormalities. Results: The cohort consisted of 7 men and 23 women, mean age 48, 93 (DS+/-12.1). PFTs resulted abnormal only in 2 patients. A DLCO reduction was observed in 54.5% of ACPA-positive subjects without RA, in 60% and in 55.6% of patients with early and established RA, respectively. In RA patients, an inverse correlation between disease duration and DLCO/Va (r=-0.50; p=0.03) was observed. The exercise tolerance at CPET was reduced in 54.5% of ACPA-positive subjects without RA, in 20% of patients with early RA and in 55.6% of those with established RA. Serum SP-D levels were higher in established RA (p=0.079), in ACPA-positive subjects and early RA than in healthy controls. ACPA levels positively correlated (r=0.45;p=0.01) with CPET parameters of ventilation inefficiency, suggesting a ventilation/perfusion mismatch. A negative correlation between ACPA and SP-D levels and CPET metabolic parameters was also observed. The presence of pulmonary nodules was the most common alteration founded at HRCT, equal to 28% in ACPA-positive subjects without arthritis, in 66% and 87% of patients with early and established RA, respectively. In the last group, all patients showed parenchymal abnormalities. There was also a significant (p=0.022) higher frequency of lung abnormalities in patients with established disease compared with the other two groups. Conclusions: The early lung involvement in RA is often subclinical and baseline PFT's are scarcely informative. Although preliminary, these findings suggest that DLCO, CPET parameters and SP-D can represent early markers of the subclinical lung injury. Furthermore, lung abnormalities detectable at HRCT seem to develop early in the course of the disease. However, additional studies are needed to clarify lung abnormalities in RA. Disclosure of Interest: None declared